Poverty reduction strategy in Indonesia - Masduki (2014)
As long as this is understood, so the severity of the problem of poverty has to be decomposed and solved.This is due to multispektrum of the meaning of poverty, so the definition and measurement is not easily accomplished in one sense only.In more detail, the theoretical study on the conception of poverty in depth by classifying the definition and measurement of poverty in four perspectives (Laderchi,, 2003: 247 -262).First.monetary approach, Second, the approach capability, Third, the approach of social exclusion Fourth, the perspective of participatory methods. If mapped, the weakness can be explained as follows: first, anti-poverty policies implemented uniformly (general) without linking with social context, economics, and culture in each region (community).Secondly, the handling of antipoverty programs had bureaucratization too deep, so many have failed due to the entanglement procedure is too long., Third last but not least, antipoverty policies are often politically motivated diboncengi very thick, so it has no meaning for the poor socio-economic strengthening. Some things are worth paying attention to is a matter of addressing poverty linkages in accordance with the concept of cultural context, poverty is not just the size of the monetary aspects (income) alone, the involvement of the poor to define and decide the programs that fit their needs, and the failure of bureaucracy to lead and run well of anti-poverty programs. Hence the principles of sustainable development will be achieved if supported by good governance (good governance).Good governance is considered good if the resources and public issues managed effectively, efficiently which is a response to the needs of the community.